Optimalisasi Kemampuan Berpikir Tingkat Tinggi Siswa pada Tingkat Sekolah Menengah Atas (SMA) di Yogyakarta - Rabiatul Adawiyah; Dwi Purbowati (Borneo Journal of Science and Mathematics Education, 2021)
The purpose of this study was to see the optimization of higher order thinking skills of students at the high school level in Yogyakarta by using the service learning model in biology learning, especially in schools using the 2013 curriculum. This study was a quasi-experimental with a pretest-posttest noneequivalent control group design. The population was all students of class X IPA at SMAN 1 Godean, SMAN 2 Nganglik and SMAN 1 Kalasan. Sampling using convenience sampling technique. Analysis of higher order thinking skills using Anderson Krathwohl's taxonomic indicators at the level of analyzing (C4) and evaluating (C5) were analyzed using the ANAKOVA test at the 0.05 significance level.